FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN NON-KEUANGAN PADA BURSA EFEK INDONESIA - Hendra; Suryanto (E-Jurnal Akuntansi TSM, 2023)
As of March 2022, there are 783 companies that have conducted an IPO on the Indonesia Stock Exchange. Investors need to analyze the company's value to find out the company's performance. This study was conducted to determine the effect of the dependent variable on Firm Value on the independent variables Return on Assets, Debt to Assets Ratio, Current Ratio, Firm Size, Dividend Payout Ratio, Assets Growth, Assets Management, and Audit Committee. The object of this study is a non-financial company listed on the Indonesian stock exchange from 2019 – 2021 as a population. The sampling method used in this study is purposive sampling and the method for analyzing data used multiple regression method. There were 93 companies and 279 data that passed the criteria. This study states Return on Assets and Debt to Assets Ratio have a positive effect on Firm Value. The current Ratio has a negative effect on firm value. Firm Size, Dividend Payout Ratio, Assets Growth, Assets Management, and Audit Committee have no effect on Firm Value.